Examining Community Service in Preschool Management: The Learning Processes of biMBA AIUEO Through a Literature Review - Tyna Yunita; Uswatun Khasanah; Murti Wijayanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Discussions about early childhood are always interesting, as they relate to future generations. Children's educational achievements today will determine their success in the future. Nonetheless, the number of early childhood children (ages 0–6) enrolled in preschool education in Indonesia remains significantly restricted. Therefore, biMBA, as a preschool educational institution, plays a very important role in shaping children's future success. This study aims to identify promising research areas through a literature review and determine the factors influencing preschool-aged children's learning at biMBA AIUEO. The findings show discussions on four topics: (1) learning processes, (2) human resource management, (3) marketing strategies, and (4) learning facilities. The teacher unit of analysis has the highest quantity, highlighting the role of educators in the preschool environment as parental figures who significantly influence children's development, especially during the formative years when independence is instilled. The findings indicate that pedagogical approaches are crucial for early childhood education and are an interesting subject to research because of their significance to (a) cognitive development and (b) socio-emotional development